The Effect of Market linkage on Growth of Micro and Small-Scale Enterprises: The Case of Botor Tolay Woreda, Oromia Regional State, Ethiopia - Susi, Elias (International Journal of Entrepreneurship and Project Management, 2023)
Purpose: The aim of the study was to assess the effect of market linkage on growth of Micro and Small-Scale Enterprises: The Case of Botor Tolay Woreda, Oromia Regional State, Ethiopia. Methodology: The study was adopted descriptive and explanatory research design and Use Both Quantitative and qualitative research approach. The primary and secondary data was used, the primary data was collected by using questionnaires and interviews. Since the total 369 MSE operators from 2010-2015 EC, 192 sample size were selected using stratified and simple random technique with Yemane Formula. The collected data was analyzed by using descriptive and inferential statistics. To ensure the relationship between independent and dependent variables the Pearson correlation and multiple linear regression was applied. The data was analyzed by using Statistical package for Social Science (SPSS) version 25. The study Result was presented through the using of table and figures. Finding: The study focuses on the seven major factors that affect the growth of MSE that were Access to Market Information, Access to finance, Government support, Infrastructure, Entrepreneurial competency, Social Network, and types of business sectors. The findings of correlation and regression show that there was a positive and significant relationship between MSEs' growth and, Access to Market Information, Access to finance, Government Support, Infrastructure Entrepreneurial Competency, Social Network, and types of business sectors and also, lack of adequate market linkage. Unique Contribution to Theory, Policy and Practice: Based on the finding the researcher recommended that the government body should facilitate market linkage to ensure the existing market linkage policy, develop infrastructure, and provide support for MSE. The Entrepreneurs Practice on their side to develop their Competency and Social Networks. In addition, sufficient market information should be collected continuously to increase the linkage to the market. The finding aligned with the theory of Resource base view, the institutional theory and social network theory.